The Role Development of Academic Nurse Leaders: A Qualitative Descriptive Study - DelPrete, Jacklyn S (Nursing education perspectives, 2025)
The aim of this study was to provide comprehensive and holistic insight into nurse faculty role development as academic nurse leaders (ANLs) in the United States. There are gaps in knowledge surrounding ANL role development despite studies on the efficacy of specific programs on leadership development for nursing faculty. Using a qualitative descriptive methodology with research questions framed by Kolb's experiential learning theory, 18 participants with one year or more of experience in their current academic nursing leadership role were interviewed. Through qualitative descriptive content analysis, three themes emerged about the role development of ANLs: looking within, overcoming challenges, and becoming a successful leader. The findings of this study offer new insights into ANL role development including the power of self-reflection, overcoming imposter syndrome, understanding the change in student and faculty dynamics, and creating a network of support.